Guided Growth of the Proximal Femur for the Management of Hip Dysplasia in Children With Cerebral Palsy. Issue 8 (September 2019) - Portinaro, Nicola; Turati, Marco; Cometto, Matteo; Bigoni, Marco; Davids, Jon R.; Panou, Artemisia
Abstract : Background: Progressive hip displacement is one of the most common and debilitating deformities seen in children with cerebral palsy (CP). The aim of this study was to evaluate the results of temporary medial hemiepiphysiodesis of the proximal femur (TMH-PF) using a transphyseal screw to control hip migration during growth in children with CP. Methods: This was a retrospective study of children with CP and hip dysplasia, age 4 to 11 years and GMFCS levels III-V. There were 28 patients with 56 hips that underwent TMH-PF surgery between 2007 and 2010. Clinical and radiologic evaluation was performed preoperatively, at 6, 12, and 60 months following the index surgery. Acetabular index (AI), neck-shaft angle (NSA) and migration percentage (MP) were measured. All complications were recorded. Results: All radiographic measurements were significantly improved at the final follow-up. Positive correlations were found between NSA, MP, and AI. Multiple regression analysis revealed that MP, time from surgery, and age were influenced by the decrease of the NSA. The femoral physis grew off the screw in 9 hips within 36 months. The screw head broke during attempted screw exchange in 1 hip. The remain cases (4 hips) were treated by placing a second screw parallel to the existing one. Finally, progressive subluxation occurred in 3 hips when the physis grew off the screw and were treated by skeletal reconstruction. Conclusions: TMH-PF was effective in controlling progressive subluxation of the hip in the majority of cases, obviating the need for major reconstructive surgery in these children with CP. Level of Evidence: Level IV.